A novel, rapid and cost-effective method for separating drug-loaded liposomes prepared from egg yolk phospholipids. (April 2022) - Jose, Joseph; Kanniyappan, Hemalatha; Muthuvijayan, Vignesh
Abstract: Liposomal drug formulations often utilize passive drug-loading methods to encapsulate drugs into the liposome. These formulations require an additional processing step to remove the unencapsulated drug, using techniques like ultracentrifugation, ultrafiltration, column chromatography, dialysis, etc. However, these methods suffer from downsides like high costs, high time consumption, low scalability, etc. In this study, we have employed solvents of varying dielectric constants to carry out this separation. Using phospholipids isolated from chicken eggs, we synthesized doxorubicin hydrochloride loaded liposomes. Utilizing solvents such as acetone and ethanol along with low-speed centrifugation, we were able to efficiently recover up to 94% of the drug-loaded liposomes, which was much higher than that achieved with conventional techniques like ultracentrifugation (11%) and ultrafiltration (89%). The morphology and size of acetone-treated liposomes, monitored using TEM and DLS analysis, were found to be intact and only slightly altered. The bilayer morphology was determined to be unaltered by solvents through XRD analysis. The absence of residual solvents was confirmed through 1 H NMR analysis. In vitro release study using doxorubicin confirmed that the release profile was similar irrespective of the separation technique. Thus, we have established a novel approach for cheaply and quickly separating egg phospholipid-based liposomes from unencapsulated drugs. Graphical Abstract: ga1 Highlights: Liposomes are usually separated from free drugs by expensive techniques. We have employed solvents to carry out this separation step. Acetone and ethanol were able to separate liposomes with around 90% efficiency. Liposomes separated by Acetone was found to be structurally & functionally unaffected.